(untitled) (Journal of Science Foundation, 2019)
Background: Correlation of actual fetal weight with clinically and ultrasonographically detected macrosomia cases among diabetic mother is very essential for the management of the neonates. Objectives: The purpose of the present study was to correlate actual fetal weight with clinically and ultrasonographically detected macrosomia cases among diabetic mother. Methodology: This cross-sectional study was carried out in inpatient Department of Obstetrics and Gynecology and in outpatients Department of Radiology and Imaging, BIRDEM during the period of April 2005 to March 2007. Pregnant women with diagnosed diabetes mellitus (DM) or gestational diabetes mellitus (GDM) selected for caesarean section or induction of labour, gestational age 236 weeks having 23700 gm by clinical method were included in this study. First clinical estimation of fetal weight was done by the investigator then Radiologist estimated the fetal weight without knowing the EFW by clinical method. The actual birth weight was estimated after the birth of the babies. Result: The mean (+SD) age of the patients was 30.8±5.1 years ranged from 20 to 40 years. A significant correlation (r=0.5081; p<0.05) was found between clinically estimated fetal weight (gm) and actual birth weight (macrosomia) (gm). Significant correlation (r=0.6199; p<0.05) was found between sonographically estimated fetal weight (gm) and actual birth weight (macrosomia) (gm). Significant correlation (r=0.4863; p<0.05) was found between clinically estimated fetal weight (gm) and sonographically estimated fetal weight (gm). Conclusion: The study findings indicate that clinical method can be used instead of ultrasonography for prediction of macrosomia in diabetic mother Journal of Science Foundation 2018;16(2):38-44